2020
DOI: 10.3390/ani10030369
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant ESBL/AmpC-Producing Klebsiella pneumoniae Isolated from Healthy Thoroughbred Racehorses in Japan

Abstract: Extended-spectrum β-lactamase (ESBL)- and AmpC β-lactamase (AmpC)-producing Klebsiella spp. have become a major health problem, leading to treatment failure in humans and animals. This study aimed to evaluate the presence of ESBL/AmpC-producing Klebsiella spp. isolated from racehorses in Japan. Feces samples from 212 healthy Thoroughbred racehorses were collected from the Japan Racing Association Training Centers between March 2017 and August 2018. ESBL/AmpC-producing Klebsiella spp. were isolated using select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Intrinsically, E. coli is resistant to penicillin, and acquired resistance to β-lactams is mostly mediated by the production of β-lactamases such as TEM-1, TEM-2, SHV-1, and AmpC β-lactamase [ 18 ]. Resistance due to ESBL-producing E. coli and Klebsiella pneumoniae has been reported in TB racehorses in our previous studies [ 26 , 27 ]. But in South Korea and Portugal, resistance to ABPC in E. coli is reportedly lower than that in this study (3.9%, 2/51, and 4.2%, 3/71, respectively) [ 7 , 20 ].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Intrinsically, E. coli is resistant to penicillin, and acquired resistance to β-lactams is mostly mediated by the production of β-lactamases such as TEM-1, TEM-2, SHV-1, and AmpC β-lactamase [ 18 ]. Resistance due to ESBL-producing E. coli and Klebsiella pneumoniae has been reported in TB racehorses in our previous studies [ 26 , 27 ]. But in South Korea and Portugal, resistance to ABPC in E. coli is reportedly lower than that in this study (3.9%, 2/51, and 4.2%, 3/71, respectively) [ 7 , 20 ].…”
Section: Discussionmentioning
confidence: 92%
“…This study was part of a monitoring study of AMR bacteria isolated from healthy TB racehorse fecal samples in Japan. At the same time, the presence of extended-spectrum β-lactamase (ESBL)- and AmpC β-lactamase-producing bacteria and AMR enterococci was also investigated as per our previous reports [ 25 , 26 , 27 ]. Though this study used the same samples as our previous studies, the isolation and identification of E. coli were conducted using protocols that were independent from those used in our previous study about ESBL-producing E. coli that were isolated using a selective agar medium containing an antibiotic (1 µ g/m l cefotaxime).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar cohort of healthy horses from Canada, the number of staff members and equestrian event participation were identified as risk factors for MDR E. coli shedding [ 13 ]. In a study from Japan, healthy racehorses were reported to be colonized with MDR ESBL/AmpC-producing Klebsiella pneumoniae [ 14 ]. Another unique horse population that AMR pathogens were recovered from was equine destined for human consumption in Spain, in which both nasal and fecal carriage of a highly virulent MRSA was detected [ 15 ].…”
mentioning
confidence: 99%